APPLICATION OF INTRAOPERATIVE FROZEN SECTION IN SECOND-STAGE REIMPLANTATION FOR CHRONIC PERIPROSTHETIC HIP JOINT INFECTION (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the application of intraoperative frozen section (FS) and analyze its association with reinfection in second-stage revision arthroplasty for patients with chronic periprosthetic hip joint infection.Materials and Methods: A prospective case series study was conducted on 39 patients with chronic PJI who underwent two-stage revision arthroplasty at Cho Ray Hospital between January 2021 and November 2025. FS was routinely performed during the second stage using five periprosthetic tissue samples, with a negative threshold defined as
Keywords: Frozen section; periprosthetic joint infection; two-stage revision; reinfection.